2018
DOI: 10.1111/jvh.12974
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and vaccination coverage of Hepatitis B among healthcare workers in Cameroon: A national seroprevalence survey

Abstract: Hepatitis B virus (HBV) infection is hyperendemic in Cameroon, and healthcare workers (HCWs) are at high risk of infection. We aimed to assess prevalence, risk factors and vaccine coverage of HBV infection among HCWs in Cameroon. We conducted a cross‐sectional study in 16 hospitals across all regions of Cameroon. HCWs were tested for HBV using rapid diagnostic tests (RDT). We collected data on socio‐demographics and HBV vaccination status. We estimated prevalence of HBV and used Poisson regression models with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
7
8
2
Order By: Relevance
“…This study revealed a relatively high burden of current HBV infection (10.6%) among HCWs in Cameroon. The high prevalence of HBV in this study population is similar to the HBV prevalence obtained in a similar study carried out in Yaoundé,24 but higher than the 8.7% obtained in a national survey among HCWs 30. The difference in the prevalence of HBV could be due to the different diagnostic techniques used.…”
Section: Discussionsupporting
confidence: 82%
“…This study revealed a relatively high burden of current HBV infection (10.6%) among HCWs in Cameroon. The high prevalence of HBV in this study population is similar to the HBV prevalence obtained in a similar study carried out in Yaoundé,24 but higher than the 8.7% obtained in a national survey among HCWs 30. The difference in the prevalence of HBV could be due to the different diagnostic techniques used.…”
Section: Discussionsupporting
confidence: 82%
“…This might be due to differences in socioeconomic status and standards of health care services. Our estimate is also lower than other African countries such as Kenya, Nigeria, and Libya [ 6 ], but higher than the national prevalence of 11.4% of Cameron [ 41 ]. This might be because the cost and unavailability of vaccination might be the reason for the low coverage [ 6 , 17 ].…”
Section: Discussioncontrasting
confidence: 69%
“…On the other hand, 48.4% of the study participants have received at least one dose of HBV vaccine. This finding is higher than a study done in Cameroon (11.4%) [ 30 ] but lower than Northern Tanzania (67.4%) [ 31 ], Kenya (80%) [ 32 ], Malaysia (95.91%) [ 33 ] and Pakistan (73.42%) [ 34 ]. This difference could be due to the unavailability of the HBV vaccine for adults above 18 years in Ethiopia [ 35 ].…”
Section: Discussioncontrasting
confidence: 57%